2000
DOI: 10.1046/j.1523-1747.2000.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inheritance of Mutations in the Uroporphyrinogen Decarboxylase and Hemochromatosis Genes Accelerates the Onset of Porphyria Cutanea Tarda

Abstract: Porphyria cutanea tarda is a skin disease caused by photosensitization by porphyrins whose accumulation is caused by deficiency of hepatic uroporphyrin- ogen decarboxylase activity. Mutations in the uroporphyrinogen decarboxylase gene are present in the low-penetrant, autosomal dominant familial form but not in the commoner sporadic form of porphyria cutanea tarda. We have investigated the relationship between age of onset of skin lesions and mutations (C282Y, H63D) in the hemochromatosis gene in familial (19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 58 publications
5
37
1
8
Order By: Relevance
“…9 People homozygous for this mutation with hemochromatosis have up to 60-fold greater risk of having PCT53 and have earlier onset of skin lesions. 18 In southern Europe, another mutation in the hemochromatosis gene which also may be associated to PCT is H63D. 60 Viral infections -The role of hepatotropic viruses in triggering PCT has been reported since 1992.…”
Section: Triggerrring Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 People homozygous for this mutation with hemochromatosis have up to 60-fold greater risk of having PCT53 and have earlier onset of skin lesions. 18 In southern Europe, another mutation in the hemochromatosis gene which also may be associated to PCT is H63D. 60 Viral infections -The role of hepatotropic viruses in triggering PCT has been reported since 1992.…”
Section: Triggerrring Factorsmentioning
confidence: 99%
“…Many Urod mutations (more than 40) in the 1p34 chromosome diminish enzyme stability or cause altered pre-RNAm splicing. 1,7,14,18 It is an autosomic dominant disorder with low clinical penetrance; less than 10% of affected subjects are symptomatic. 15 As most individuals who inherit the enzyme defect do not manifest the disorder, it is suggested that additional genetic or non-genetic factors are needed for expressing the disease.…”
Section: Introductionmentioning
confidence: 99%
“…A presença destas mutações no gene HFE tem sido largamente estudada nos doentes com PCT que apresentam uma elevada frequência da mutação C282Y em homozigotia (entre 11 e 47% nos estudos realizados na maioria dos países da Europa e EUA) 3,4,12,13 . Um estudo no norte da Itália demonstrou também uma incidência significativamente aumentada da mutação H63D nos doentes com PCT 3,4,13,14 .…”
Section: Caso Clínicounclassified
“…Há formação nas células hepáticas de um inibidor competitivo desta enzima no fígado, por um mecanismo ferro-dependente 1 . Por esta razão é considerada uma doença ferro-dependente, e pelo menos 80% dos doentes apresenta siderose hepática, embora menos de 20% tenha o diagnóstico concomitante de hemocromatose 3 . Lesões bolhosas numa mulher de pele bronzeada…”
Section: Introductionunclassified
“…[1][2][3] PCT patients usually display hepatic siderosis, and the disease is responsive either to phlebotomy, which presumably acts through iron depletion, or a treatment with low-dose chloroquine or hydroxychloroquine. 1,2 In addition, some PCT patients have quite high levels of hepatic iron associated with the common mutations in the HFE gene (C282Y and H63D), 4,5 which are also found in hereditary hemochromatosis (type I).…”
mentioning
confidence: 99%